Breaking The 3T Barrier: Smart Teacherpreneurs of Harapan Island - Kadarisman; Siswanto, Romi; Akadira, Tora; Zulfikri; Fatmasari, Rhini; Mudayat; Budi, Untung Laksana (Pascasarjana Universitas Mataram, 2025)
Strengthening teacher capacity in 3T areas requires an approach that goes beyond conventional pedagogical training by integrating entrepreneurial competencies, differentiated learning, and leveraging local potential. This study presents a teacherpreneur training model for elementary/middle school/community learning center teachers on Harapan Island, Thousand Islands, which is operationalized through a convergent mixed-methods design. The design incorporates attendance measurement, multi-component evaluation scores, and qualitative findings from observations and structured interviews. Field data shows 22 participants from various schools, an attendance rate of 83%, and a distribution of quiz, case study, and practice scores indicating substantial competency achievement in the dimensions of creativity, utilization of local potential, partnership networks, and educational entrepreneurship practices. The integration of quantitative and qualitative findings confirms the relevance of the training to the island context, which faces limitations in infrastructure, technology access, and professional development opportunities. The discussion links the findings to current literature on teacherpreneurial competence, partnership management, differentiated instruction, and digital-based service-learning practices. This study offers theoretical implications for the construction of teacherpreneur competencies and practical implications for program replication in other 3T regions. The recommendations emphasize strengthening post-training mentoring, orchestrating local networks, and digital portfolio-based reporting for sustainable impact.